The equation are x-3y=-13 and 2x+15y=16.
The coefficients of y is not equal in both equations.
Multiply the equation x-3y=-13 by 5.
![\begin{gathered} 5(x-3y)=-13\cdot5 \\ 5x-15y=-65 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/asd6gmxuux7zu025m5ty5om6ac6vb7ddfr.png)
Add the equation 5x-15y=-65 and 2x+15y=16 to eliminate the y.
![\begin{gathered} 5x-15y+2x+15y=-65+16 \\ 7x=-49 \\ x=-(49)/(7) \\ =-7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j3dxqqepjkdyranvhxnj6asseu8v9fwksi.png)
Substitute 7 for x in the equation x-3y=-13 to obtain the value of y.
![\begin{gathered} -7-3y=-13 \\ -3y=-13+7 \\ y=(-6)/(-3) \\ =2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lz7gt0j6t446nywt97di3yhigtycyfepkn.png)
The solution of the equations is (-7,2).